La lucha for Cuba : religion and politics on the streets of Miami - De La Torre, Miguel A. (Berkeley : University of California Press, 2003)
For many in Miami's Cuban exile community, hating Fidel Castro is as natural as loving one's children. This hatred, Miguel De La Torre suggests, has in fact taken on religious significance. In La Lucha for Cuba, De La Torre shows how Exilic Cubans, a once marginalized group, have risen to power and privilege--distinguishing themselves from other Hispanic communities in the United States--and how religion has figured in their ascension.
Illustrations; Abbreviations; Preface; 1. An Ajiaco Christianity; 2. La Lucha: The Religion of Miami; 3. Psalm 137: Constructing Cuban Identity while in Babylon; 4. Machismo Creating Structures of Oppression; 5. The End of the Elián Saga: The Continuation of La Lucha; Notes; References; Index.
Includes bibliographical references (pages 161-169) and index.
Print version record.
JSTOR
Keywords: Cuban Americans -- Florida -- Miami -- Politics and government; Cuban Americans -- Florida -- Miami -- Religion; Cuban Americans -- Florida -- Miami -- Social conditions; Exiles -- Political activity -- Florida -- Miami; Exiles -- Religious life -- Florida -- Miami; Exiles -- Florida -- Miami -- Social conditions; Christianity and politics -- Florida -- Miami; Oppression (Psychology) -- Political aspects -- Florida -- Miami; Miami (Fla.) -- Politics and government; Miami (Fla.) -- Religious life and customs; Américains d'origine cubaine -- Floride -- Miami -- Religion; Américains d'origine cubaine -- Floride -- Miami -- Conditions sociales; Christianisme et politique -- Floride -- Miami; Oppression -- Aspect politique -- Floride -- Miami; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; RELIGION -- Comparative Religion; Christianity and politics; Cuban Americans -- Politics and government; Cuban Americans -- Religion; Cuban Americans -- Social conditions; Exiles -- Political activity; Oppression (Psychology) -- Political aspects; Politics and government; Florida -- Miami